Penindakan Pelanggaran Terstruktur, Sistematis dan Masif pada Pilkada 2020, Menimbulkan Norma Baru: Studi Kasus: Pemilihan Wali Kota Bandar Lampung 2020 - Jaya Hasiholan Limbong (Jurnal Adhyasta Pemilu, 2021)
This study aims to reveal the existence of violations of the Bandar Lampung Mayor Election in 2020, which was carried out by the wife of the Mayor "Eva Dwiana" or often called "Mother Eva" as Candidate Pair Number 3. normatively from the legal and empirical literature from a political perspective, by coming to the TSM Violation Trial as well as through the TSM Violation Virtual Trial. Where to look deeper, a conceptual case approach is also used. Based on the results of the study, it was found that there were violations in the 2020 Bandar Lampung Mayoral Election (Pilwalkot) by Bawaslu, findings these violations were in the form of providing necessities, transportation money for family welfare empowerment, and there was the use of access to the husband's position as the incumbent mayor. Previously it had been found guilty of committing a Structured, Systematic and Massive Administrative Violation (TSM) by the Lampung Province Bawaslu, not long ago the disqualification was canceled by a judge at the Supreme Court level and gave rise to a new norm, namely reports must be at 07.00 to 13.00 which indirectly directly amend the General Elections Supervisory Agency Regulation Number 8 of 2020 concerning Handling of Violations in the Election of Mayors and Deputy Mayors on the provisions of the day which states that the day is 24 hours long. Based on these findings, law enforcement must be based on a view of the reality that occurs in society, not only from regulation. From the point of view of the reality that happens in the community, not only from regulation.